UHPC160 with ultrahigh bonding strength as well as preparation method and application of UHPC160
By using bond-reinforced composite admixture, skeleton stacking densification mix design, composite fiber system bond reinforcement technology and interface treatment method for enhanced bonding in bridge maintenance and reinforcement, a UHPC160 with ultra-high bond strength was developed. , solves the problems of high construction difficulty, poor bonding performance and high material cost in the prior art, and achieves efficient and durable bridge maintenance and reinforcement effects.
Patent Information
- Application Number
- CN202411656210.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-07-18
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-18
AI Technical Summary
In the maintenance and reinforcement of bridges, the existing technology has technical problems such as small construction site, difficult to implement special interface treatment methods, poor bonding performance and durability of repair materials, and high cost and difficult application of new high-performance repair and reinforcement materials.
Adopt reinforced composite admixture compound technology, skeleton stacking densification mix ratio design, composite fiber system bonding reinforcement technology and enhanced bonding interface treatment method are used to form a UHPC160 with ultra-high bonding strength.
Under the condition of constant traffic opening, the UHPC160's 28d ultimate bonding strength can reach 15.8MPa, the 28d compressive strength can reach 168.5MPa, and the expansion degree can reach 810mm, significantly reducing the construction difficulty of maintenance and reinforcement projects, improving construction quality and durability, and reducing construction quality and durability. Project cost.
Smart Images

Figure CN119462018A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ultra-high performance concrete, and in particular to UHPC160 with ultra-high bonding strength, and a preparation method and application thereof. Background Art
[0002] With the vigorous promotion of my country's infrastructure, rapid economic development, the gradual expansion of transportation networks, and the improvement of urban construction, my country's construction focus has gradually shifted to remote mountainous areas. As a key project in mountain transportation infrastructure, the bridge-tunnel ratio has increased year by year. The number of bridges in my country has exceeded 780,000, and most of the concrete bridges have been aged and damaged, which has a serious impact on safety and durability. Concrete bridges are damaged during use due to the atmospheric environment, load or self-performance degradation, especially cross-river and cross-sea bridges. The main reasons are: (1) external erosion environment, such as concrete carbonization, chloride ion corrosion, sulfate corrosion, freeze-thaw cycles, etc.; (2) low structural design bearing capacity and overloaded vehicles; (3) construction factors, such as low concrete strength and loose vibration; (4) earthquakes, floods, explosions and other disasters. Concrete structural defects can lead to huge safety hazards and economic losses. American scholars have proposed the "five-fold rule", which means that for every $1 saved in the design stage, an additional $5 will be spent on reinforcement in the later stage. If cracks occur, an additional $25 will be required, and as high as $125 in the case of severe damage. Concrete repair and reinforcement has become a branch of structural engineering. After concrete repair and reinforcement, the new and old concrete should work together as a whole. Good interface bonding is the key to concrete repair and reinforcement. Research on the bonding performance of new and old concrete has received widespread attention from the engineering community at home and abroad.
[0003] At present, the main technical measures to improve the bonding performance of new and old concrete at home and abroad are: (1) Various interface treatment methods to improve interface roughness Interface treatment refers to removing the damaged, loose and attached impurities and debris on the old concrete bonding surface, and exposing the solid part of the aggregate to increase the specific surface area and form a rough surface to improve the bonding strength. At present, the main methods for improving the roughness of the interface surface treatment at home and abroad are artificial chiseling, high-pressure water jetting, sandblasting, steam spraying, steel brushing, acid etching, etc. Artificial chiseling is convenient, simple, fast, low-cost and easy to operate, but the interface adhesion is poor; high-pressure water jetting, sandblasting, and steam spraying have greatly improved the interface adhesion, but the construction site requirements are high and require specific mechanical equipment and consumables, the cost is high, the technology is complex, and it is difficult to promote and apply; acid etching is a chemical method used when the construction site is limited, making it difficult to apply other methods. The interface adhesion is poor and corrodes the steel bars. Therefore, the current interface treatment methods at home and abroad have certain shortcomings.
[0004] (2) Use new high-performance repair and reinforcement materials Conventional concrete or mortar as repair and reinforcement materials have problems such as high brittleness, poor toughness, low bonding strength, and poor durability. When used in repair and reinforcement projects, the bonding strength of the repaired area is low, and it is easy to become hollow and cracked, resulting in secondary repairs. At present, new high-performance repair and reinforcement materials are mainly used at home and abroad, such as polymer cement-based composite repair materials, ultra-strong and high-toughness steel wire mesh resin concrete, etc. However, new high-performance repair and reinforcement materials are expensive, complex in process, and have few standards and specifications for related construction control, making them difficult to promote and apply.
[0005] In view of the shortcomings of technical measures for improving the bonding performance of new and old concrete at home and abroad, the inventors have developed the following four key technologies after years of research and a large number of engineering applications: A. Compounding technology of bonding-enhancing composite admixtures; B. Skeleton stacking densification mix design; C. Composite fiber system bonding enhancement technology; D. Interface treatment method for enhanced bonding.
[0006] The inventors integrated the above technologies to form a UHPC160 with ultra-high bonding strength and its preparation method. Compared with the repair and reinforcement materials currently used at home and abroad, its 28d ultimate bonding strength can reach 15.8MPa, 28d compressive strength can reach 168.5MPa, and expansion can reach 810mm. After 7d and 28d new and old concrete bonding strength tests, the concrete damage surface is the original concrete, and the bonding surface is not damaged. Moreover, under the condition of continuous road opening, only the artificial chiseling method can be used for repair and reinforcement, which significantly reduces the construction difficulty of the repair and reinforcement project, improves the construction quality of the repair and reinforcement project, speeds up the construction period, and reduces the project cost. In particular, it solves the technical problems of small construction site under the condition of continuous road opening of the repair and reinforcement project, the difficulty of implementing special interface treatment methods, poor bonding performance and durability of repair materials, and high cost and difficult application of new high-performance repair and reinforcement materials, and has been successfully applied to many engineering examples, which has important engineering practical significance. Summary of the invention
[0007] The purpose of the present invention is to address the technical difficulties in the prior art such as small construction site under the condition of continuous road opening for maintenance and reinforcement projects, poor bonding performance and durability of repair materials, high cost and difficult application of new high-performance repair and reinforcement materials, etc. The present invention provides a UHPC160 with ultra-high bonding strength and a preparation method thereof. The ultra-high bonding UHPC160 can be repaired and reinforced under the condition of continuous road opening by only using artificial roughening and a small pump. The 28d ultimate bonding strength can reach 15.8MPa, the 28d compressive strength can reach 168.5MPa, and the expansion can reach 810mm. After 7d and 28d new and old concrete bonding strength tests, the concrete failure surfaces are all original concrete, and the bonding surfaces are not damaged, meeting the application requirements of good plasticity and toughness, low engineering cost, high anti-disturbance performance, strong bonding performance, and excellent durability.
[0008] To achieve the above object, the technical solution adopted by the present invention is: A preparation method of UHPC160 with ultra-high bonding strength mainly consists of a bonding enhancement type composite admixture compounding method, a skeleton stacking densification mix ratio design method, and a composite fiber system bonding enhancement method.
[0009] Furthermore, the above-mentioned bonding enhanced composite admixture compounding method adopts ultra-dispersed, high water-reducing, bonding enhanced polycarboxylic acid superplasticizer, introduces air entraining agent, defoamer, and foam control agent, breaks large bubbles, and forms tiny stable bubbles with a diameter of less than 100 μm, supplemented by polyether shrinkage-reducing water-reducing agent additives that can reduce concrete shrinkage, and a glue-reducing agent that can reduce the amount of cement, and finally compounded to form a bonding enhanced composite admixture for ultra-high bonding strength UHPC160. Furthermore, the above-mentioned skeleton stacking densification mix design method mainly consists of ultrafine powder dense stacking design and aggregate system dense stacking design; The ultrafine powder dense packing design adopts the maximum dense skeleton packing theory, and uses micron-level ultrafine powders and nano-level ultrafine powders of different microscopic particle sizes to fill the gaps in cement particles, thereby ensuring that the workability, mechanical properties, volume stability and thermal properties of UHPC160 are excellent, while reducing the amount of cement and the porosity, improving the density of UHPC160, and forming the most dense powder skeleton; The dense packing design of the aggregate system is based on the dense packing design of ultrafine powder. The particle shape, material and gradation of the aggregate of UHPC160 are optimized and adjusted through design experiments. The aggregate system with low cement dosage, high density and guaranteed strength is selected in combination with test data.
[0010] Furthermore, the micron-sized ultrafine powder has a specific surface area of ≥800m 2 / kg high-fineness microbeads; the nano-scale ultrafine powder has a specific surface area of ≥20000m2 / kg of high fineness silica fume.
[0011] Furthermore, the above composite fiber system bonding enhancement method includes: for special parts with high bonding performance requirements, improving the bonding strength through composite fiber system design and fiber parameter design; The composite fiber system design is to design the optimal spacing and orientation of the fibers by doping or multi-doping organic metal fibers of various sizes, so as to reduce the amount of organic metal fibers, solve the problem of fiber agglomeration, and improve the bonding strength and workability; The fiber parameter design is to optimize the fiber material type, fiber technical parameters, fiber dosage, etc. through design experiments, so as to reduce the dosage of organic metal fibers, solve the problem of fiber agglomeration, and improve the bonding strength and workability.
[0012] Furthermore, the above-mentioned fiber material types include hook type and straight wire type; the fiber technical parameters include: fiber aspect ratio and tensile strength.
[0013] In a second aspect, the present application provides a UHPC160 with ultra-high bonding strength, characterized in that it is prepared by the preparation method according to any one of claims 1-6.
[0014] Furthermore, the above-mentioned UHPC160 can simultaneously achieve the following technical indicators under the condition of a disturbance frequency of 4.8HZ: the 28d ultimate bonding strength can reach 15.8MPa, the 28d compressive strength can reach 168.5MPa, and the expansion can reach 810mm; after 7d and 28d new and old concrete bonding strength tests, the concrete failure surfaces are all original concrete, and the bonding surfaces are not damaged.
[0015] In a third aspect, the present application provides a construction method without special interface treatment, which comprises: The interface to be treated only needs to be roughened manually, loose layers need to be removed, debris needs to be cleaned, and it needs to be washed and moistened. Moreover, since the ultra-high bonding UHPC160 obtained by any one of claims 1 to 6 has ultra-high fluidity, high-quality and fast construction can be achieved by only using a small pump or mortar pump.
[0016] The design concept of this application is described below: A. Compounding technology of bonding enhanced composite admixture: The present invention provides the preparation requirements of bonding enhanced composite admixture of ultra-high bonding UHPC160, which is characterized by adopting ultra-dispersed, high water-reducing, bonding enhanced polycarboxylic acid superplasticizer, introducing high-quality air entraining agent, defoamer, and foam control agent, breaking large bubbles, forming a large number of tiny stable bubbles within 100 μm, supplemented by polyether shrinkage-reducing water-reducing agent additives that can reduce concrete shrinkage, and a glue-reducing agent that can reduce the amount of cement, and finally compounding a bonding enhanced composite admixture for ultra-high bonding strength UHPC160; B. Skeleton stacking densification mix design: It is characterized by being mainly composed of ultrafine powder dense stacking design and aggregate system dense stacking design; (1) The present invention provides a design technology for dense packing of ultrafine powders, characterized in that the maximum dense skeleton packing theory is adopted, by selecting micron-sized (such as high-fineness microbeads, with a specific surface area of ≥800m 2 / kg), nanometer level (such as high-fineness silica fume, specific surface area ≥ 20000m 2 / kg) and other ultrafine powder mineral admixtures of different microscopic particle sizes fill the gaps in cement particles to ensure that the workability, mechanical properties, volume stability and thermal performance of UHPC160 are excellent, while minimizing the amount of cement and porosity, maximizing the density of UHPC160 and forming the most dense powder skeleton; (2) The present invention provides a dense packing design technology for aggregate systems, which is characterized in that, based on the dense packing design of ultrafine powders, experiments are designed to optimize the particle shape, material, grading, etc. of UHPC160 aggregates, and the aggregate system with the least cement dosage, the highest density, and the guaranteed strength is selected in combination with the test data.
[0017] C. Composite fiber system bonding enhancement technology: Furthermore, for special parts with high bonding performance requirements, the bonding strength can be further improved through composite fiber system design and fiber parameter design; (1) The present invention provides a composite fiber system design technology, characterized in that the optimal spacing and orientation of the fibers are designed by doping or multi-doping organic metal fibers of various sizes, giving full play to the fiber characteristics, thereby reducing the amount of organic metal fibers, solving the problem of fiber agglomeration, and improving bonding strength and workability; (2) The present invention provides a fiber parameter design technology, characterized in that the fiber material type (hook type, straight wire type, etc.), fiber technical parameters (fiber aspect ratio, tensile strength, etc.), fiber dosage, etc. are optimized through design experiments to reduce the amount of metal fiber, solve the problem of fiber agglomeration, and improve bonding strength and workability; D. A construction technology without special interface treatment method using the above-mentioned ultra-high bonding UHPC160, characterized in that the interface only needs to be roughened manually, loose layers are removed, debris is cleaned, cleaned and moistened, and due to the ultra-high fluidity of ultra-high bonding UHPC160, only a small pump or mortar pump can be used for high-quality and fast construction; The UHPC160 with ultra-high bonding strength produced by this inventive concept can speed up the construction period of maintenance and reinforcement projects, improve project quality, and reduce project costs. In particular, it solves the technical problems of small construction sites under the condition of continuous road opening for maintenance and reinforcement projects, difficulty in implementing special interface methods, poor bonding performance and durability of repair materials, and high cost and difficult application of new high-performance repair and reinforcement materials. It has been successfully applied to many engineering examples and has important engineering practical significance.
[0018] Due to the adoption of the above technical solution, the beneficial effects of the present invention are: (1) Ultra-high bonding performance. An ultra-high bonding UHPC160 prepared by the above technology has a 28d ultimate bonding strength of up to 15.8MPa, a 28d compressive strength of up to 168.5MPa, and an expansion of up to 810mm. After 7d and 28d bond strength tests of new and old concrete, the concrete failure surfaces are all original concrete, and the bonding surface is not damaged; (2) High anti-disturbance performance. An ultra-high bonding UHPC160 prepared by the above technology can be constructed under the condition of continuous traffic (test disturbance frequency is 4.8HZ); (3) Ultra-high durability. An ultra-high bonding UHPC160 prepared by the above technology has a high degree of structural densification, good structural density, excellent impermeability, crack resistance, corrosion resistance and volume stability, and reduces the cost of secondary maintenance in the later period; (4) Construction with simple interface treatment method. An ultra-high bond UHPC160 prepared by the above technology can be repaired and reinforced only by artificial roughening method and meet engineering technical requirements; (5) High-quality, convenient and fast construction. The ultra-high bonding UHPC160 prepared by the present invention has the characteristics of high bonding strength, strong anti-disturbance performance, excellent durability, good plasticity and toughness, etc. It can be constructed quickly and with high quality without interrupting traffic by using small pumping equipment and simple interface treatment methods; (6) Significant economic benefits. The present invention directly reduces cement costs, steel fiber costs, road breaking construction costs, construction period, etc., and also improves the plasticity and toughness of UHPC160, significantly improves its bonding strength and durability, and ultimately extends the service life of the structure, saving reinforcement and maintenance costs during the service life, while improving the safety of the structure; (7) Improved ecological benefits. The present invention involves technologies such as significantly reducing the amount of cement and steel fiber used, continuous construction, and no special interface treatment methods, which reduces the environmental pollution, manpower and material resources caused by the production of cement, steel fiber and other materials and special interface treatment methods, and improves the ecological benefits of the project. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1Example 1 Performance comparison test of UHPC160 prepared with bonding enhanced composite admixture and conventional admixture; Figure 2 Example 2 Performance comparison test of UHPC160 prepared by skeleton densification mix design and conventional mix design; Figure 3 Example 3 compares the performance of UHPC160 prepared by using composite fiber system bonding reinforcement technology and conventional fiber system design. DETAILED DESCRIPTION
[0020] The present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.
[0021] Raw material selection: (1) Cement: P·Ⅱ52.5 cement with a specific surface area of 390m 2 / kg, 3d / 28d flexural strength 6.2MPa / 8.3MPa, 3d / 28d compressive strength 34.1MPa / 58.7MPa; (2) Fly ash microspheres: specific surface area 1300m 2 kg -1 , water requirement ratio 95%; (3) Silica fume: SiO2 content 86.3%, water requirement ratio 109%, 7d / 28d activity index 100% / 112%; (4) Expansion agent: Calcium-magnesium composite expansion agent, with a limited expansion rate of 0.026 / 0.012 in water for 7 days / in air for 28 days.
[0022] (5) Copper-coated steel fiber: diameter range 0.12mm~0.20mm (steel fibers of various diameters), length range 8~24mm (steel fibers of various lengths), tensile strength ≥2700MPa; (6) Inorganic fiber: diameter 0.15 mm, length 12 mm, tensile strength 1000 MPa; (7) Fine aggregate: quartz sand, 20-140 mesh; zone II machine-made sand, fineness modulus 3.05; natural sand, fineness modulus 3.12; (8) Coarse aggregate: 5-10 mm continuous graded basalt, parent rock strength 204.1 MPa, crushing value 6.7%; (9) Additives: polycarboxylic acid superplasticizers and various water reducing agent additives; (10) Water: water for domestic use.
[0023] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0024] Example 1 Study on UHPC160 Bond Enhanced Composite Admixture Using the above raw materials, by adopting ultra-dispersible, high water-reducing, bonding-enhanced polycarboxylic acid superplasticizer, introducing high-quality air entraining agent, defoamer, foam control agent, polyether shrinkage-reducing water-reducing agent, glue-reducing agent and other water-reducing agent additives, a bonding-enhanced composite admixture was compounded. UHPC160 was prepared with the bonding-enhanced composite admixture, and the workability, mechanical properties and durability were compared with those of UHPC160 prepared with conventional admixtures.
[0025] Table 1 UHPC160 mix ratio (kg / m 3 ) Remark: A1 conventional admixtures are: 41% polycarboxylic acid water reducer + 0.15‰ air entraining agent + 0.1‰ defoamer; A2 composite admixture is: 26% polycarboxylic acid superplasticizer + 0.05‰ air entraining agent + 0.05‰ defoaming agent + 4% glue reducing agent + 6% polyether shrinkage reducing water reducing agent + 0.05‰ foam stabilizer.
[0026] Table 2 UHPC160 performance indicators Group A2 used a special composite admixture for bonding-enhanced UHPC compounded by technical measures to prepare bonding-enhanced UHPC160. Figure 1 It can be seen that compared with conventional UHPC160 (Group A1), the amount of UHPC admixture in Group A2 was reduced by 23.1%, the 28d drying shrinkage rate was reduced by 16.6%, and the workability, mechanical properties, crack resistance, and volume stability were all greatly improved, especially the 28d ultimate bonding strength was increased by 17.9%.
[0027] The bonding-enhanced composite admixture has a higher water reduction rate and can effectively control and reduce the internal porosity of UHPC to further reduce the amount of admixture and improve the compactness of UHPC, thereby significantly enhancing the performance of UHPC.
[0028] Example 2 Study on the mix design of skeleton densification Based on the use of bonding enhanced composite admixtures, densely packed UHPC160 is prepared by densifying the ultrafine powder system and aggregate system with the least cement dosage, the highest density and guaranteed strength. The workability, mechanical properties and durability are compared with those of UHPC with conventional mix design.
[0029] Table 3 UHPC160 mix ratio (kg / m 3 ) Remark: In the B1 conventional mix design group, the fine aggregate is all quartz sand (20-40 mesh quartz sand); In the B2 skeleton densification mix design group, the fine aggregate is quartz sand (20-40 mesh quartz sand): (40-70 mesh quartz sand): (70-140 mesh quartz sand): machine-made sand = 6.5:1:2:0.5.
[0030] Table 4 Concrete performance index Group B2 used a skeleton densification mix design to prepare densely packed UHPC160. Figure 2 It can be seen that compared with the conventional mix design of UHPC160 (Group B1), the total amount of cementitious materials in Group B2 UHPC160 is reduced by 50kg / m 3 Under such circumstances, workability, mechanical properties, crack resistance and volume stability are still significantly improved, the 28d ultimate bonding strength is increased by 17.9%, the 28d compressive strength is increased by 3.4%, the 28d flexural strength is increased by 15.4%, the 28d drying shrinkage rate is reduced by 10.0%, the expansion is increased from 740mm to 780mm, and the early crack resistance is improved from L-Ⅳ to L-Ⅴ.
[0031] The skeleton densification mix design is based on the micron-sized powder (such as high-fineness micro-beads, with a specific surface area of ≥800m 2 / kg), nano-powder (such as high-fineness silica fume, specific surface area ≥ 20000m 2 / kg), cement particles, fine aggregates with mesh sizes of 10 to 200, and other materials with different particle sizes are optimally combined at the "micro-meso" scale to maximize the density of UHPC and reduce its porosity. Then, an expansion source is introduced to further expand and fill the pores to form the densest structure, thereby significantly improving various performances.
[0032] Example 3 Research on bonding and reinforcement technology of composite fiber system On the basis of the technologies described in Examples 1 and 2, a composite fiber system bonding reinforcement technology is adopted. The bonding strength is further improved through the composite fiber system design and fiber parameter design to prepare fiber-reinforced UHPC, and the workability, mechanical properties and durability are compared with those of conventional fiber system UHPC.
[0033] Table 5 UHPC160 mix ratio (kg / m 3 ) Remark: In the C1 conventional fiber system, the fibers are: steel fibers with a diameter of 0.16 mm and a length of 13 mm; In the C2 composite fiber system, the fibers are: 10kg of steel fibers with a diameter of 0.12mm and a length of 8mm + 70kg of steel fibers with a diameter of 0.20mm and a length of 13mm + 40kg of steel fibers with a diameter of 0.20mm and a length of 20mm + 1kg of inorganic fibers.
[0034] In groups C1 and C2, the fine aggregates are quartz sand (20-40 mesh quartz sand): (40-70 mesh quartz sand): (70-140 mesh quartz sand): machine-made sand = 6.5:1:2:0.5.
[0035] Table 6 Concrete performance indicators Based on the technology described in Examples 1 and 2, Group C2 used composite fiber system bonding reinforcement technology to prepare ultra-high bonding UHPC160. Figure 3 It can be seen that compared with the conventional fiber system UHPC160 (C1 group), the fiber dosage of C2 group UHPC160 is reduced by 39kg / m 3 Under these conditions, the 28d ultimate bond strength increased by 18.8%, the 28d flexural strength increased by 11.8%, and the 28d drying shrinkage decreased by 14.9%. In addition, the reduction in fiber dosage is also beneficial to the homogeneity and workability of UHPC.
[0036] The above technology is achieved by dual or multi-doping organic metal fibers and inorganic fibers of various sizes ranging from 8 to 24 mm to design the optimal fiber spacing, optimal orientation, and optimal technical parameters, so as to give full play to the fiber characteristics, reduce the amount of metal fibers, solve the problem of fiber agglomeration, and improve bonding strength and workability.
[0037] Example 4 A construction technology without special interface treatment method using the above ultra-high bonding UHPC160, characterized in that the interface only needs to be roughened manually, loose layers are removed, debris is cleaned, cleaned and moistened, and due to the ultra-high fluidity of ultra-high bonding UHPC160, only a small pump or mortar pump can be used for high-quality and fast construction; Example 5 The UHPC160 with ultra-high bonding strength prepared by the technology described in Examples 1 to 4 was successfully applied to the maintenance and reinforcement project of the Minjiang Second Bridge in Yibin in December 2023, achieving high-quality and rapid construction without special interface treatment methods (only artificial roughening method) under high-frequency disturbance conditions. After on-site sampling and measurement, the 28d ultimate bonding strength of UHPC160 reached 15.8MPa, the 28d compressive strength reached 168.5MPa, and the expansion reached 800mm. After 7d and 28d new and old concrete bonding strength tests, the concrete damage surfaces were all original concrete, and the bonding surfaces were not damaged, which significantly improved the reinforcement and durability of the maintenance and reinforcement materials, extended the service life of the structure, and saved the reinforcement and maintenance costs during the service life.
[0038] The original repair material of the Yibin Minjiang Second Bridge maintenance and reinforcement project, ultra-high-toughness steel mesh resin concrete (HTRCS), had a total cost of about RMB 22.916 million, while the total cost of using UHPC140 was about RMB 2.8 million, saving a total of RMB 20.116 million in material costs alone.
[0039] Table 7 Comparison of economic benefits Table 8 Comparison of repair and reinforcement materials for the Second Minjiang Bridge The above-described embodiments are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention are included in the protection scope of the present invention.
Claims
1. A method for preparing UHPC160 with ultra-high bonding strength, characterized in that: It mainly consists of a compounding method of bonding and reinforcing composite admixtures, a skeleton stacking densification mix design method and a bonding and reinforcing method of a composite fiber system.
2. The method for preparing UHPC160 with ultra-high bonding strength according to claim 1, characterized in that: The bonding enhancement composite admixture compounding method adopts an ultra-dispersible, high water-reducing, bonding enhancement polycarboxylic acid superplasticizer, introduces an air entraining agent, a defoamer, and a foam control agent, breaks large bubbles, forms tiny stable bubbles with a diameter of less than 100 μm, and is supplemented with a polyether shrinkage-reducing water-reducing agent that can reduce concrete shrinkage, and a glue-reducing agent that can reduce cement dosage, and finally compounds a bonding enhancement composite admixture for ultra-high bonding strength UHPC160.
3. The method for preparing UHPC160 with ultra-high bonding strength according to claim 1, characterized in that: The skeleton packing densification mix design method mainly consists of ultrafine powder dense packing design and aggregate system dense packing design; The ultrafine powder dense packing design adopts the maximum dense skeleton packing theory, and uses micron-level ultrafine powders and nano-level ultrafine powders of different microscopic particle sizes to fill the gaps in cement particles, thereby ensuring that the workability, mechanical properties, volume stability and thermal properties of UHPC160 are excellent, while reducing the amount of cement and the porosity, improving the density of UHPC160, and forming the most dense powder skeleton; The dense packing design of the aggregate system is based on the dense packing design of ultrafine powder. The particle shape, material and gradation of the aggregate of UHPC160 are optimized and adjusted through design experiments. The aggregate system with low cement dosage, high density and guaranteed strength is selected in combination with test data.
4. The method for preparing UHPC160 with ultra-high bonding strength according to claim 3, characterized in that: The micron-sized ultrafine powder has a specific surface area of ≥800m 2 / kg high-fineness microbeads; the nano-scale ultrafine powder has a specific surface area of ≥20000m 2 / kg of high fineness silica fume.
5. A method for preparing UHPC160 with ultra-high bonding strength as claimed in claim 1, characterized in that: The composite fiber system bonding enhancement method comprises: for special parts with high bonding performance requirements, improving the bonding strength through composite fiber system design and fiber parameter design; The composite fiber system design is to design the optimal spacing and orientation of the fibers by doping or multi-doping organic metal fibers of various sizes, so as to reduce the amount of organic metal fibers, solve the problem of fiber agglomeration, and improve the bonding strength and workability; The fiber parameter design is to optimize the fiber material type, fiber technical parameters, fiber dosage, etc. through design experiments, so as to reduce the dosage of organic metal fibers, solve the problem of fiber agglomeration, and improve the bonding strength and workability.
6. The method for preparing UHPC160 with ultra-high bonding strength according to claim 5, characterized in that: The fiber material types include hook type and straight wire type; the fiber technical parameters include: fiber aspect ratio and tensile strength.
7. A UHPC160 with ultra-high bonding strength, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 6.
8. The UHPC160 with ultra-high bonding strength according to claim 7, characterized in that: The UHPC160 can simultaneously achieve the following technical indicators under the condition of a disturbance frequency of 4.8HZ: 28d ultimate bonding strength can reach 15.8MPa, 28d compressive strength can reach 168.5MPa, and expansion can reach 810mm; after 7d and 28d new and old concrete bonding strength tests, the concrete failure surfaces are all original concrete, and the bonding surfaces are not damaged.
9. A construction method without special interface treatment, characterized in that: It includes: The interface to be treated only needs to be roughened manually, loose layers need to be removed, debris needs to be cleaned, and it needs to be washed and moistened. Moreover, since the ultra-high-bonding UHPC160 obtained according to any one of claims 1 to 6 has ultra-high fluidity, high-quality and fast construction can be achieved by only using a small pump or a mortar pump.